Combined oral contraceptives: optimal survey complex - Рыкова, О. В. (REPRODUCTIVE ENDOCRINOLOGY, 2018)
Combined oral contraceptives (COCs) are effective drugs for contraception and the treatment of reproductive disorders in polycystic ovary syndrome (PCOS). The recommendation of using COCs according to the WHO guidelines “Medical eligibility criteria for using contraceptives” (5th edition, 2015) should begin with an assessment of the presence of risk factors that will help identify the group of women with high risks of complications from taking these drugs. This is an assessment of the risks of thrombosis (venous and arterial) based on history, genetic testing data, age, smoking, medical status, the presence of several diseases and other risk factors: hypertension, migraine with aura, obesity, diabetes mellitus with vascular complications, severe diseases of the liver, blood, systemic lupus erythematosus, postpartum status. Based on these data, all women who are considered to be prescribing СOC will be ranked into four eligibility groups. This will determine for which women this method of contraception will be absolutely acceptable (category 1), and for whom it is unacceptable and other methods of contraception should be recommended (category 4). To select these drugs as first-line treatment of reproductive disorders in PCOS, it is necessary to evaluate not only the presence of the above risk factors for the development of complications, but also to carry out a differential diagnosis of the main diseases that have a similar clinical picture, however, require specific treatment. This is a pathology of the thyroid gland, hyperprolactinemia, САН (21 hydroxylase deficiency), Cushing’s syndrome, acromegaly and a number of other, more rare diseases. Laboratory methods are used to screen and diagnose these diseases. Based on the guidelines of the specialized world organizations in Europe and America, algorithms for laboratory diagnosis of the main endocrinopathies are described. Particular attention is paid to factors influencing hormone levels, the rules for taking analysis and interpretation of the results.